Monkey Business: The Victorian Natural History Museum, Evolution, and the Medieval Manuscript - Rogers, Janine; Holmes, John (Romanticism on the Net, 2018)
Victorian natural history museums (NHMs) incorporated sophisticated theories of literate culture through their architectural, artistic and cultural strategies; these literary gestures were fundamental to science communication in the nineteenth century. Victorian architects looked to the cultural and artistic pasts of classical, medieval and renaissance Europe as inspiration for artistic, cultural and social values: most obviously, in the medievalism of the Gothic Revival. The idea of the “medieval,” or a more generalized mythic past, shaped the development of NHMs that in the nineteenth century were wrestling with the idea of the past in biological science—specifically the idea of an evolutionary past. These two concepts of history—literary-historical and evolutionary-scientific—intersect in critical ways in the Victorian NHM. This paper will explore how Victorian medievalism interprets biological science through the built environment of the NHM, and will explain how these interpretations are essentially literary in nature. We will give special attention to the use of marginal figures in British, European and Canadian museums, specifically the Oxford University Museum (1860), the British Museum (Natural History), London (1881)—now known as the Natural History Museum—and the Naturhistorisches Museum in Vienna (1889), as well as an Art Deco homage to the Victorian neo-Gothic museum tradition, the Royal Ontario Museum (1914 & 1933). These carved and painted figures of plants and animals were at once part of the museum design and references back to the marginalia of the medieval manuscript. We will explore how this medieval literary motif impacts on nineteenth-century scientific interpretation in the built space of the NHM, with special attention to the depiction of monkey figures in these marginal spaces, and their symbolic function in the larger interpretive framework for understanding evolutionary science and our place in the natural world.